DEVELOPING BILINGUAL STUDENT WORKSHEET FOR SEVENTH-GRADE STUDENTS AT SMP N 3 TEMBUKU - Ni Kadek Sribek; Pande Agus Adiwijaya; Luh Made Dwi Wedayanthi (Journal on Studies in English Language Teaching (JOSELT), 2022)
This study aims to develop a bilingual student worksheet for the seventh-grade students at SMP N 3 Tembuku. This study utilized the research and development design by Sugiyono (2017). There were 5 stages in the design of this research, including identification of potential problems, literature study and information gathering, product design, design validation, and testing design. The research subjects were teachers and students of seventh grade based on curriculum 2013 at SMP N 3 Tembuku. The development object was a bilingual student worksheet for seventh-grade students at SMP N 3 Tembuku. Validation was done by experts who were lecturers at ITP Markandeya Bali and one of the English teachers at SMP N 3 Tembuku. The level of validation of the student worksheet was analyzed with descriptive statistics using a Likert scale. The design was approved with several revisions, including adjustments in the learning objectives and learning indicators. The results obtained in the developing bilingual student worksheet for seventh-grade students at SMP N 3 Tembuku got excellent results with a mean score of 66.67. The first expert scored 63, the result of the second expert was 64, and the result of third expert was 73 from the interval scale which had been set.